CARBON, OXYGEN AND STRONTIUM ISOTOPES IN PALEOZOIC CARBONATE COMPONENTS: AN EVALUATION OF ORIGINAL SEAWATER-CHEMISTRY PROXIES - Brand U. (My University, 2004)
Brachiopods, trilobites, cements and whole rock (=matrix) material were evaluated for their reliability as proxies of original seawater carbon, oxygen and strontium isotope chemistry. In this process, coeval material was evaluated from individual horizons of formations spanning the Permian to Cambrian.Unaltered shells of low-Mg calcite articulated brachiopods, retain original seawater oxygen, carbon and strontium isotope compositions, as old as late Ordovician. Assessments of older specimens are hampered by a lack of suitable material (coeval brachiopod–whole rock sets). A definitive assessment of cement marine chemistry is difficult due to the paucity of material, but despite this caveat, cements hold some promise for retaining original carbon and possibly strontium isotope seawater values. In contrast, the potential of whole rock material as a proxy of original seawater chemistry is quite complex. In some, but not all instances, the carbon isotopic composition of whole rock, after detailed scrutiny and evaluation, appears to represent an original seawater chemistry signal. In a few instances, their oxygen isotope compositions reflect original seawater values. Unlike the stable isotope compositions, the strontium isotopes of all studied whole rock material (Permian to upper Cambrian) appear not to reflect original seawater chemistry values. Thus the potential for retaining original seawater isotope chemistry and serving as specific proxies, in order of decreasing reliability, are (1) unaltered low-Mg calcite brachiopods (C, O and Sr isotopes), (2) pristine marine cements (C and Sr isotopes), and (3) whole rock material (C isotopes?).Carbon, oxygen and strontium isotope compositions of Ordovician trilobites mirror those of coeval unaltered brachiopods. Cambrian trilobites hold significant promise as an important proxy of original seawater isotope chemistry but further studies are needed to ascertain their full potential. The survey of isotopes in some Ordovician and Cambrian intermediate/low-Mg calcite trilobites demonstrates their potential as an important proxy of original seawater chemistry.
Keywords: Brachiopods; Trilobites; Cement; Matrix-whole rock; Carbon; Oxygen and strontium isotopes; Original seawater-chemistry proxies; Paleozoic; Paleozoic; Палеозой